Cross‐cultural adaptation, reproducibility and validation of the Italian version of the Patient and Observer Scar Assessment Scale (POSAS). Issue 6 (6th August 2017) - Vercelli, Stefano; Ferriero, Giorgio; Bravini, Elisabetta; Stissi, Valeria; Ciceri, Matteo; Rossetti, Sara; Bianchi, Sara; Sartorio, Francesco
ABSTRACT: The Patient and Observer Scar Assessment Scale (POSAS) is one of the most robust instruments to assess scar quality, but there is no Italian version, and no other competing instruments are available in Italian. The aim of this study was to translate and validate an Italian version of POSAS (POSAS‐I). POSASv2.0 was culturally adapted in accordance with international standards. The psychometric assessment included acceptability/feasibility, internal consistency, reproducibility, construct validity and sensitivity to change. Cultural equivalence of POSAS‐I with the English version was confirmed. The validation study included 102 subjects with surgical scars. Both subscales demonstrated acceptable internal consistency (Cronbach's α = 0·72–0·80). Reproducibility of the OSAS‐I (ICCs = 0·93–0·94; SEM = 1·8 points; MDC95 = 5·1 points) was superior to that of PSAS‐I (ICC = 0·65; SEM = 5·7 points; MDC95 = 15·7 points). OSAS‐I showed moderate to good correlations with the Vancouver Scar Scale (VSS), Global Rating of Change Scale (GRCS) and PSAS‐I. Sensitivity to change was large for PSAS‐I (effect size = 1·08; standardised response mean = 0·96) and moderate to large for OSAS‐I (ES = 0·69; SRM = 0·92). This study confirmed that POSAS‐I can be used to assess patients with surgical scars in the Italian population. OSAS‐I is useful for clinical and research purposes, while PSAS‐I should be better used to capture patients' own opinions and symptoms in clinical settings.